2018
DOI: 10.3390/ijms19082351
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium graminearum ATP-Binding Cassette Transporter Gene FgABCC9 Is Required for Its Transportation of Salicylic Acid, Fungicide Resistance, Mycelial Growth and Pathogenicity towards Wheat

Abstract: ATP-binding cassette (ABC) transporters hydrolyze ATP to transport a wide range of substrates. Fusarium graminearum is a major causal agent of Fusarium head blight, which is a severe disease in wheat worldwide. FgABCC9 (FG05_07325) encodes an ABC-C (ABC transporter family C) transporter in F. graminearum, which was highly expressed during the infection in wheat and was up-regulated by the plant defense hormone salicylic acid (SA) and the fungicide tebuconazole. The predicted tertiary structure of the FgABCC9 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…A possible mechanism has been suggested by Kerr et al, (1999) that involves a reduction in camp in hyphae formation [36]. The treatment with pyocyanin resulted also in a decrease in the secretion of the B-trichothecenes mycotoxins, Deoxynivalenol (DON) and Nivalenol (NIV) by the fungi, re- flecting the protective role of pyocyanin on wheat plant against infections which is comparable to the study done by [15].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…A possible mechanism has been suggested by Kerr et al, (1999) that involves a reduction in camp in hyphae formation [36]. The treatment with pyocyanin resulted also in a decrease in the secretion of the B-trichothecenes mycotoxins, Deoxynivalenol (DON) and Nivalenol (NIV) by the fungi, re- flecting the protective role of pyocyanin on wheat plant against infections which is comparable to the study done by [15].…”
Section: Discussionsupporting
confidence: 64%
“…graminearum has 62 ABC transporter genes, which are divided into seven families (A-G) according to domain architecture and phylogenetic data [14]. FgABC9, an ABC-C transporter gene with an MRP domain, is involved in the export of salicylic acid by F. graminearum and in the fungal response to tebuconazole and pathogenesis in wheat [15]. Qi PF et al, (2018) have shown that the deletion of FgAB-CC9 led to a decrease in mycelial growth, a reduction in the accumulation of deoxynivalenol (DON), and consequently to a less pathogenicity towards wheat [15].…”
Section: List Of Abreviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have indicated the roles of multiple ATP-binding cassette transporters or major facilitator superfamily (MFS) proteins in virulence activities of the fungi such as Botrytis cinerea, Cochliobolus carbonum, Cercospora kikuchii, Fusaria, Magnaporthe grisea, Mycosphaerella graminicola and Penicillium digitatum [83][84][85][86][87][88][89][90][91][92]. The same applies to F. graminearum, ATP-Binding Cassette Transporter Gene FgABCC9 was found to be involved in the fungus's pathogenicity towards wheat [93]. F. graminearum attacks its host plant through the secretion of mycotoxins characterized as virulence factors.…”
Section: Pathogenicity and Virulence Factors Of Fusarium Graminearummentioning
confidence: 99%